Uncommon Bis-Amide Matrine-type Alkaloids From Sophora alopecuroides With Anti-inflammatory Effects - Luo, Ding; Tu, Zhenchao; Yin, Wenjing; Fan, Chunlin; Chen, Nenghua; Wu, Zhongnan; Ding, Weilong; Li, Yaolan; Wang, Guocai; Zhang, Yubo (Frontiers in Chemistry, 2021)
Four new alkaloids (1−4) belong to rare examples of bis-amide matrine-type were isolated from the seeds of sophora alopecuroides. Their structures including absolute configuration were determined by extensive spectroscopic analysis, electronic circular dichroism (ECD) interpretation, and X-ray diffraction crystallography. Chemically, bis-amide matrine-type alkaloids can provide new molecular template for structural modification. Compounds 3−4 displayed obvious anti-inflammatory effects based on the inhibition of two key pro-inflammatory cytokines [tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6)] in a dose-dependent manner, with IC50 values from 35.6 to 45.8 μm.